2012
DOI: 10.1530/joe-12-0207
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses HIF1A synthesis and VEGFA release in pituitary adenomas

Abstract: Curcumin (diferuloylmethane), a polyphenolic compound derived from the spice plantCurcuma longa, displays multiple actions on solid tumours including anti-angiogenic effects. Here we have studied in rodent and human pituitary tumour cells the influence of curcumin on the production of hypoxia inducible factor 1α (HIF1A) and vascular endothelial growth factor A (VEGFA), two key components involved in tumour neovascularisation through angiogenesis. Curcumin dose-dependently inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…An important contributor to tumors propensity to invade and metastasize is angiogenesis. Cell lines derived from surgically resected pituitary adenomas treated with curcumin have decreased HIF1A and VEGFA, both of which are involved in tumoral angiogenesis [56]. …”
Section: Mechanism and Preclinical Datamentioning
confidence: 99%
“…An important contributor to tumors propensity to invade and metastasize is angiogenesis. Cell lines derived from surgically resected pituitary adenomas treated with curcumin have decreased HIF1A and VEGFA, both of which are involved in tumoral angiogenesis [56]. …”
Section: Mechanism and Preclinical Datamentioning
confidence: 99%
“…Previous research from Shan found that curcumin inhibits the synthesis of hypoxia-induced mRNA and secretion from VEGFA in GH3 cells and the culture of pituitary adenoma cells in humans supports the suppressive effect on neovascularization of pituitary tumors (25). Several other cancer studies have also stated that curcumin suppresses VEGF expression in Ehrlich tumor ascites cells and NIH3T3 cells (26), in pancreatic tumors (16), and in ovarian cancer (27).…”
Section: Discussionmentioning
confidence: 85%
“…The present study shows that in vivo inhibition of the NF-jB pathway not only reduced cell proliferation, but also increased apoptosis in GH3 tumours growing in nude mice. NFjB inhibitors were suggested to reduce tumour progression by their suppressive effects on tumour neovascularisation (47,48). Therefore, we cannot rule out that the effect of BAY on GH3 cell turnover in vivo is additionally mediated through other mechanisms (i.e.…”
Section: Discussionmentioning
confidence: 97%